COVID-19 pandemic: Impacts on mothers' and infants' mental health during pregnancy and shortly thereafter. (January 2022) - Vardi, Noa; Zalsman, Gil; Madjar, Nir; Weizman, Abraham; Shoval, Gal
The COVID-19 pandemic brought about a global crisis, with profound implications on public mental health. The current review focuses on the impact of the pandemic on the mental health of mothers and their infants during pregnancy and shortly after delivery. Literature shows that in similar disaster situations, mothers' stress reaction and mental health have a critical impact on infant development. Research data on perinatal mental health during the current COVID-19 pandemic is reviewed in conjunction with studies on the relationship between maternal stress, infant development, and psychopathology. Recommendations for perinatal mental health enhancement are discussed and topics for future research suggested.